2021
DOI: 10.1002/cphc.202000883
|View full text |Cite
|
Sign up to set email alerts
|

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature

Abstract: We study the interaction and metalation reaction of a free base 5,10,15,20‐terakis(4‐cyanophenyl)porphyrin (2HTCNPP) with post‐deposited Zn atoms and the targeted reaction product Zn‐5,10,15,20‐terakis(4‐cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…This conformation differs from the square symmetry of the conventional “saddle-shaped” configuration in which the two iminic nitrogens are almost parallel to the substrate’s surface. The saddle conformation is typically found in porphyrins on less reactive substrates such as Ag(111). , Our DFT calculations find that the saddle shape is 0.86 eV higher in energy (less stable) than the inverted structure on Cu(111), explaining why our STM images at RT only show rectangular-shaped molecules.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…This conformation differs from the square symmetry of the conventional “saddle-shaped” configuration in which the two iminic nitrogens are almost parallel to the substrate’s surface. The saddle conformation is typically found in porphyrins on less reactive substrates such as Ag(111). , Our DFT calculations find that the saddle shape is 0.86 eV higher in energy (less stable) than the inverted structure on Cu(111), explaining why our STM images at RT only show rectangular-shaped molecules.…”
Section: Resultsmentioning
confidence: 61%
“…On Cu(111), however, our STM measurements clearly show that the molecules in the metal–organic framework (MOF) assume the inverted conformation. This finding is interesting because usually porphyrin molecules in 2D networks on metallic surfaces adopt a molecular structure with a low diffusion barrier, ,, and the studies involving porphyrins in inverted conformations reported recently do not present any ordered motifs with the molecule in this configuration. , This demonstrates the importance of this new growth protocol. The 2D hexagonal arrangement shown in Figure b has an experimental lattice angle α ≈ 62 ± 3°.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the self-assemblies CN-groups are oriented at 90 • angle to the axis of the cyanophenyl ring of a neighboring molecule, as observed on other substrates before [10,32,62,63]. For the stabilization of the supramolecular assembly via the CN-groups [64] hydrogen bonding to the pyrrole group [62] or the phenyl rings [32] has to be considered.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…As a bottom-up approach, on-surface synthesis has demonstrated its great potentials in constructing low-dimensional molecular nanostructures and materials with atomic precision. , Moreover, recent advances in scanning probe microscopes allows probing on-surface chemical reaction processes at the single chemical bond level. It has been demonstrated that porphyrins can undergo a number of reactions on the surface to form porphyrinoids and related hybrid nanostructures that are hardly accessible in conventional solution chemistry (Table S1). Most of these reactions are based on the reactivity at the β- and meso -positions (Figure a). For example, thermal treatment of fluorinated tetraphenylporphyrins on the Au(111) surface can induce intramolecular cyclization of the β-pyrrolic carbon with the ortho -carbon and thus form five-membered rings attached to the molecules.…”
mentioning
confidence: 99%